RUSSIAN ENGINEERING TEACHERS AS AN IMPORTANT PART OF IGIP - A. N. SOLOVYEV; V. M. PRIKHODKO; T. Yu. POLYAKOVA; Z. S. SAZONOVA (Высшее образование в России)
The paper highlights the milestones of the history of the International Society for Engineering Pedagogy (IGIP) from 1972 until now. Professor A. Melezinek was a founder of the society; he developed its structure that survived to the present time. Now his pedagogical ideas are being developed and revised to reflect the changes in the goals and contents of engineering education, new methods, means of training and control, modern communication capabilities. Global challenges, problems of sustainable development and construction of the so-called “Resilient Society” were the main topics of the last Annual IGIP conferences. Globalization has led to the organization of the International Federation of Engineering Education Societies (IFEES). IGIP was one of its founders in 2006. We discuss different aspects of cooperation between Russian technical universities and IGIP, which began in 1995. Regional IGIP conferences and round tables are one of the aspects of such cooperation. The importance of this interaction for the Russian scientific school of engineering education is emphasized.